2020
DOI: 10.31234/osf.io/mt3p4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological Correlates of COVID-19 Conspiracy Beliefs and Preventive Measures: Evidence from Turkey

Abstract: COVID-19 pandemic has led to popular conspiracy theories regarding its origins and widespread concern over the level of compliance with preventive measures. In the current preregistered research, we recruited 1,088 Turkish participants and investigated (a) individual differences associated with COVID-19 conspiracy beliefs; (2) whether such conspiracy beliefs are related to the level of preventive measures; and (3) other individual differences that might be related to the preventive measures. Higher faith in in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 0 publications
5
49
1
1
Order By: Relevance
“…A few other causes were identified from this review: ideology ( Chou et al., 2021 ; Okereke et al., 2020 ; Scherer and Pennycook, 2020 ; Ghazal Aghagoli et al., 2020 ; Cichocka, 2020 ; Hauer and Sood, 2020 ), health information needs and overloads ( Greenspan and Loftus, 2021 ; Morgan-Daniel et al., 2020 ; Garcia and Duarte, 2020 ; Larson, 2020 ), civil literacy ( Schiavo, 2020 ), the armchair scientist phenomenon ( Chong et al., 2020 ), inappropriate usage of map information ( Mooney and Juhász, 2020 ), the distrust of government ( Mondiale de la Santé, 2020 ; Chou et al., 2021 ; Horton, 2020 ), financial incentives and lack of supervision ( Bastani and Bahrami, 2020 ), and large scale lockdown ( Kulkarni et al., 2020 ; Sasidharan et al., 2020 ; Cichocka, 2020 ). Only ideology was quantitatively investigated: people with certain ideological characteristics (e.g., general skepticism, cultural/political orientation, and conservatism) were found more susceptible to rumors ( Calvillo et al., 2020 ; Alper et al., 2020 ; Georgiou et al., 2020 ; Biddlestone et al., 2020 ; Havey, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A few other causes were identified from this review: ideology ( Chou et al., 2021 ; Okereke et al., 2020 ; Scherer and Pennycook, 2020 ; Ghazal Aghagoli et al., 2020 ; Cichocka, 2020 ; Hauer and Sood, 2020 ), health information needs and overloads ( Greenspan and Loftus, 2021 ; Morgan-Daniel et al., 2020 ; Garcia and Duarte, 2020 ; Larson, 2020 ), civil literacy ( Schiavo, 2020 ), the armchair scientist phenomenon ( Chong et al., 2020 ), inappropriate usage of map information ( Mooney and Juhász, 2020 ), the distrust of government ( Mondiale de la Santé, 2020 ; Chou et al., 2021 ; Horton, 2020 ), financial incentives and lack of supervision ( Bastani and Bahrami, 2020 ), and large scale lockdown ( Kulkarni et al., 2020 ; Sasidharan et al., 2020 ; Cichocka, 2020 ). Only ideology was quantitatively investigated: people with certain ideological characteristics (e.g., general skepticism, cultural/political orientation, and conservatism) were found more susceptible to rumors ( Calvillo et al., 2020 ; Alper et al., 2020 ; Georgiou et al., 2020 ; Biddlestone et al., 2020 ; Havey, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data from Korea indicate that while Christianity negatively impacted conspiracy beliefs, higher religiosity across religious identities was positively correlated (Kim and Kim 2021). A study from Turkey also found that increased religiosity predicted higher levels of COVID-specific conspiracy beliefs (Alper et al 2020). In a Western setting, Talia Leibowitz and her co-authors (2021) found that greater religi osity and spirituality were associated with higher specific and general conspiracy beliefs (including COVID-related) among US and Canadian respondents.…”
Section: Conspiracy Theory Religion and Covid-19mentioning
confidence: 99%
“…5 This pandemic still go on over the world, there were more than 2 million cases. 6 Some unknown aspects of the disease, such as viral, comorbidity, definitive antiviral therapy, effectiveness of vaccination's raise global concerns about this pandemic. 3 Prevention aspects was the main approach to inhibit the spread of virus.…”
Section: Discussionmentioning
confidence: 99%